Managing the COVID-19 health crisis: a survey of Swiss hospital pharmacies - Laurence Schumacher; Yassine Dhif; Pascal Bonnabry; Nicolas Widmer (BMC, 2023)
Abstract Background The COVID-19 pandemic strained healthcare systems immensely as of 2020. Switzerland's hospital pharmacies' responses during the first wave were surveyed with a view to improving the quality of pharmaceutical management in future health crises. Methods An online survey was sent to the heads of all of Switzerland's hospital pharmacies. The questionnaire was organised into eleven sections of questions covering many topics regarding the management of COVID-19's first wave. Data collection occurred from May to June 2020. Results Analyses were performed using the 43 questionnaires (66%), with at least one answer per questionnaire, out of 65 distributed. Seventeen of 41 pharmacies responding (41%) had existing standard operating procedures or pandemic plans and 95% of these (39/41) set up crisis management steering committees. Twenty-nine of 43 pharmacies responding (67%) created new activities to respond to the pandemic's specific needs. Twenty-six of 39 pharmacies responding (67%) created new drug lists for: COVID-19-specific treatments (85%; 22/26), sedatives (81%; 21/26), anaesthetics (77%; 20/26) and antibiotics (73%; 19/26). Drug availability in designated COVID-19 wards was managed by increasing existing stocks (54%; 22/41 pharmacies) and creating extra storage space (51%; 21/41). Two drugs generated the greatest concern about shortages: propofol (49%; 19/39 pharmacies) and midazolam (44%; 17/39). Remdesivir stocks ran out in 26% of pharmacies (10/39). Twelve of 43 pharmacies (28%) drafted specific new documents to respond to medical needs regarding drug administration, 12 (28%) did so for drug preparation and 10 (23%) did so for treatment choices. Conclusions Switzerland's hospital pharmacies encountered many challenges related to the COVID-19 crisis and had to find solutions quickly, effectively and safely. The survey highlighted the key role that hospital pharmacies played in many aspects of the pandemic by providing logistical and clinical support to medical and nursing care teams. The lessons and experiences outlined could be used to improve the quality of hospital pharmacies' readiness for similar future events.